Efeitos da música clássica sobre a cognição, parâmetros fisiológicos e psicológicos em idosos com demência institucionalizados - Rocha, Luana Aparecida da (2020)
Introduction: Dementias are responsible for a large part of the impairment of cognitive ability in the elderly and negatively affect functional capacity, quality of life, independence and autonomy. Thus, actions aimed at health care for the elderly should aim to control the symptoms and adverse signs resulting from chronic diseases already installed. In this way, musical intervention has been perceived as a potential alternative in reducing the progression of dementia. Objective: To analyze the effects of classical music on cognition, physiological parameters and behavioral and psychological symptoms of dementia (BPSD) in institutionalized elderly. Methodology: This is a descriptive-exploratory, quantitative, quasi-experimental study, with a Control Group (CG), to verify the effect of classical music on cognition, SCPD and physiological parameters in institutionalized elderly. Eight sessions with classical music were performed, selected by a music therapist for the Intervention Group (IG) over two months at ILPI A. For the CG (ILPI B) the headset was applied, however, without classical music. Both groups (GI and CG) were evaluated by ACE-R before and after the intervention. In addition, data on blood pressure, heart rate and heart coherence (through Cardioemotion) were obtained during music sessions. The SCPD were evaluated through the Neuropsychiatric Inventory (NPI), applied to nurses from the two participating institutions. Results: 14 elderly participants were evaluated, 7 belonged to the IG and 7 to the CG. In both groups there was a predominance of female participants, widowed marital status and diagnosed with Alzheimer's. Although not significant, most of the NPI variables improved when compared to the moments before and after for GI, with significant wear in apathy (t = 2.646; p = 0.038) and in the total mean NPI severity (t = 2.760; p = 0.033) with lower averages at the time after intervention. For the control group, no significant differences were found in the mean level of the variables in the pre and post analysis, with most of the averages remaining the same. Conclusion: Classical music provided stimuli and the possibility of improving the conditions of institutionalized elderly people as well as professionals involved in care.